Syntactic status of person markers in the Nanti language (Campa, Arawak) - Michael, Lev (2004)
This paper aims to analyze the syntactic status of person markers in the Nanti language, focusing on subject markers. The goal of this analysis is to choose between two possible types of analysis of these markers. The first type of analysis proposes that person markers are not arguments of the verb, but a form of concord or anaphoric morphology that refers to independent noun phrases. The second type of analysis proposes that person markers are arguments of the verb, and that co-referential noun phrases are not arguments of the verb, but extraposed nouns that function as topics and occupy syntactic positions distinct from the arguments of the verb. The conclusion of the present study is that person markers in the Nanti language are arguments of the verb and that they occupy syntactic positions of their own rather than forming part. of the verb. It is suggested that these markers form a single phonological word with the verb due to phonological constraints on the minimum size of phonological words in the Nanti language.